New Method of Inhibition of Activity of Tumor Necrosis Factor Alpha In Patients with Psoriasis - A. Gerasun, Borys (Recent Patents on Endocrine, Metabolic & Immune Drug Discovery (Discontinued), 2016)
Introduction: A new method of reduction of tumor necrosis factor alpha activity via intradermal immunization with inactivated autoleukocytes (patent UA97493 (2015) [1]) has been presented in the article. New patents from various countries have been analyzed [2-7]. Objective: Patients with psoriasis (24) with high level of tumor necrosis factor alpha in their blood (≥ 30pg/ml) were immunized with autoleukocytes. Method: Leukocytes were isolated by centrifuging plasma, obtained after precipitation of a patient’s heparinized peripheral venous blood. Precipitate was suspended in 1.0 - 1.5ml of a patient’s blood serum and 0.1ml of blood was injected into the skin of the back. For determination of autoleukocyte immunization efficacy, concentration of tumor necrosis factor alpha in a patient’s blood was compared prior to immunization and at different periods after immunization. Results: In 30 days after single immunization, a considerable decrease in cytokine concentration was observed in all patients (100%); it reduced to zero in 16 out of 24 of immunized individuals (66.7%). The degree of reduction and duration of the achieved effect were individual, thus, if necessary the immunization was repeated several times. The procedure was well tolerated, and general condition of patients was improved. Conclusion: The method of reduction of tumor necrosis factor alpha activity is recommended for implementation into clinical practice.
Keywords: Autoleukocytes